First Report of Apiospora arundinis Causing Leaf Spot on wheat in China - Lyu, Ruiling (Plant disease, 2025)
Wheat (Triticum aestivum L.) is one of the most important food crops. In April 2022, leaf spot disease were observed in a 1 hectare field located in the Huanggang area of Hubei, China(30°56'99″ N, 114°91'70″E). The lesions can infect the leaves and stems of wheat, initially presenting as punctate ulcerative spots . Over time, these lesions coalesce, leading to the necrosis and subsequent rotting of the stems and leaves in the field. To identify the pathogen, 30 diseased leaf pieces (5 × 5 mm) from the lesion borders were surface sterilized in 1% NaClO for 2 min, then rinsed three times with sterile distilled water. The tissues were placed on potato dextrose agar (PDA) and incubated at 25°C for 3 d in the dark. A total of 27 isolates with consistent morphological characteristics were obtained. The representative isolates HGNU2022-6 and HGNU2022-8 were used for morphological studies and phylogenetic analyses. The colonies on PDA of the two isolates were white with fluffy aerial mycelium, subsequently exhibiting yellow pigmentation. The hyphae were smooth, hyaline, branched and septate. Conidiophores were hyaline or pale brown and produced conidiogenous cells, which were pale brown, smooth, ampulliform, and 8.25 (7.53 to 12.82) μm long (n = 50). Conidia were solitary or clustered, brown or dark brown, smooth, ellipsoidal to spherical, and 11.28 (6.50 to 14.81) × 11.34 (7.17 to 14.32) μm (n = 50) in size. Based on these morphological characteristics, the fungus was identified as belonging to the genus Apiospora (Pintos and Alvarado 2021). For molecular identification, the internal transcribed spacer (ITS), translation elongation factor 1-alpha (TEF-1α) and β-tubulin 2(TUB2)genes were amplified with the primer pairs ITS1/ITS4, EF1-728F/EF-2 and T10/Bt-2b, respectively (White et al. 1990; Glass and Donaldson 1995; O'Donnell and Cigelnik 1997). The generated sequences were deposited in GenBank with accession numbers PQ135955 and PQ135957 for ITS, PQ148399 and PQ148400 for TEF-1α, and PQ148401 and PQ148402 for TUB2. All the sequences had more than 99% similarity with those of the Apiospora arundinis strain LC7252 and LC7277. In the multilocus phylogenetic analysis, the two isolates clustered together with other strains of A. arundinis with 100% bootstrap support. The two isolates were identified as A. arundinis based on morphological and molecular characteristics. For pathogenicity testing, healthy leaves of six wheat plants were inoculated with 100 μl of spore suspension (1 × 106 conidia/ml) and then incubated at 22°C, 90% relative humidity, with a 16 h light/8 h dark cycle. The inoculated leaves showed necrosis and wilt symptoms similar to those observed in the greenhouse, whereas the control leaves were asymptomatic. Apiospora arundinis was re-isolated from symptomatic plants and the identity was confirmed based on morphology and DNA sequence. No pathogenic fungus was isolated from the control leaves. The experiment was repeated six times with similar results. Currently, there are a total of 86 Apiospora arundinis records in the USDA Fungal Databases. However, wheat as a host has only been recorded in Poland. To our knowledge, this is the first report of Apiospora arundinis causing leaf blight on wheat in China. This report will help identify disease symptoms in the field and provides a basis for determining the occurrence, distribution, and control of the disease